South African Institute of Race Relations collection of political documents - Luthuli, A. J. (Albert John), 1898-1967; Mandela, Nelson, 1918- (1929)
Includes materials from the Communist Party of South Africa, the South African Communist Party, various socialist groups, and the South African Congress of Democrats; materials on Albert Luthuli and Nelson Mandela; and issues of D & A, Flash, Spark, and Information service (International Defence and Aid Fund)